Repeatability and Reproducibility of Quantitative Corneal Shape Analysis after Orthokeratology Treatment Using Image-Pro Plus Software - Ying Mei; Zhiping Tang; Zhouyue Li; Xiao Yang (Journal of Ophthalmology)
Purpose. To evaluate the repeatability and reproducibility of quantitative analysis of the morphological corneal changes after orthokeratology treatment using “Image-Pro Plus 6.0” software (IPP). Methods. Three sets of measurements were obtained: two sets by examiner 1 with 5 days apart and one set by examiner 2 on the same day. Parameters of the eccentric distance, eccentric angle, area, and roundness of the corneal treatment zone were measured using IPP. The intraclass correlation coefficient (ICC) and repetitive coefficient (COR) were used to calculate the repeatability and reproducibility of these three sets of measurements. Results. ICC analysis suggested “excellent” reliability of more than 0.885 for all variables, and COR values were less than 10% for all variables within the same examiner. ICC analysis suggested “excellent” reliability for all variables of more than 0.90, and COR values were less than 10% for all variables between different examiners. All extreme values of the eccentric distance and area of the treatment zone pointed to the same material number in three sets of measurements. Conclusions. IPP could be used to acquire the exact data of the characteristic morphological corneal changes after orthokeratology treatment with good repeatability and reproducibility. This trial is registered with trial registration number: ChiCTR-IPR-14005505.